2016
DOI: 10.1007/s40122-016-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

The 5% Lidocaine-Medicated Plaster: Its Inclusion in International Treatment Guidelines for Treating Localized Neuropathic Pain, and Clinical Evidence Supporting its Use

Abstract: When peripheral neuropathic pain affects a specific, clearly demarcated area of the body, it may be described as localized neuropathic pain (LNP). Examples include postherpetic neuralgia and painful diabetic neuropathy, as well as post-surgical and post-traumatic pain. These conditions may respond to topical treatment, i.e., pharmaceutical agents acting locally on the peripheral nervous system, and the topical route offers advantages over systemic administration. Notably, only a small fraction of the dose reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…Because topical lidocaine can penetrate no deeper than 8–10 mm, it is therefore indicated in well-localized neuropathic pain. Its efficacy has been documented in different types of localized neuropathic pain, including post-herpetic neuralgia, painful diabetic neuropathy, post-surgical and post-traumatic pain related to incision of the skin [ 19 ]. The most common adverse effects of lidocaine are mild local reactions due to its topical application.…”
Section: Second- and Third-line Drugs For Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Because topical lidocaine can penetrate no deeper than 8–10 mm, it is therefore indicated in well-localized neuropathic pain. Its efficacy has been documented in different types of localized neuropathic pain, including post-herpetic neuralgia, painful diabetic neuropathy, post-surgical and post-traumatic pain related to incision of the skin [ 19 ]. The most common adverse effects of lidocaine are mild local reactions due to its topical application.…”
Section: Second- and Third-line Drugs For Neuropathic Painmentioning
confidence: 99%
“…The most common adverse effects of lidocaine are mild local reactions due to its topical application. Lidocaine’s lack of systemic absorption and of drug interactions can be particularly beneficial in older patients [ 19 ].…”
Section: Second- and Third-line Drugs For Neuropathic Painmentioning
confidence: 99%
“…147 However the patches may in some circumstances demonstrate equivalence to systemic anti-neuropathic agents with superior tolerability. 148 Their use is recommended for consideration in frail patients, a physical state common to many cancer survivors. 149 150 A Cochrane review of low-concentration capsaicin cream found insufficient data to recommend its use in neuropathic pain, 151 whilst the high-concentration patch form also suffers from a deficiency of evidence sufficient to make confident pronouncements on its efficacy.…”
Section: Pharmacological Management Opioidsmentioning
confidence: 99%
“…Topical lidocaine absorption will also be affected by the thickness and surface area of the stratum corneum at the site of application, local vascularity and the duration of application. Typically, the maximal penetration depth of lidocaine when applied topically is from 8 to 10 mm [31]. Absorption is higher at mucosal sites [10] such as the mouth where lidocaine sprays are used for dental, anesthetic and surgical procedures.…”
Section: Lidocainementioning
confidence: 99%